A teleavaliação e telerreabilitação como habilidades clínicas do fisioterapeuta: um protocolo de revisão de escopo - Oliveira, Oziene Ramos de (Brasil, 2024)
Introduction: The evolution of digital health has driven the development of specific skills for telehealth and telerehabilitation practices, opening new possibilities for remote physiotherapeutic care. However, there is a gap in the literature regarding the clinical competencies necessary for physiotherapists to effectively implement these practices. Objective: This study aims to present a scoping review protocol that explores the clinical skills and requirements essential for teleassessment and telerehabilitation as core competencies within the physiotherapy field. Methods: The protocol will follow the Joanna Briggs Institute (JBI) guidelines and include observational studies and reviews from databases such as PubMed, CINAHL, PEDro, Scopus, Lilacs and Web of Science. Studies in English and Portuguese, published between 2014 and 2024, addressing specific technical and clinical competencies related to telehealth and telerehabilitation in physiotherapy will be considered. Screening will be conducted in two stages: title and abstract review, followed by full-text analysis. Expected Conclusion: This review is anticipated to provide a detailed overview of the clinical skills required for telehealth practices in physiotherapy, supporting the standardization and development of these competencies among physiotherapists and informing future guidelines and educational policies for the field.